Moistureproof durable medium-voltage cable and preparation method thereof
By using a combination of modified polyethylene resin and moisture-proof filler to coat the medium voltage cable, the problem of the cable being damp in humid environments is solved, and the cable is high moisture-proof and long service life is achieved.
Patent Information
- Application Number
- CN202411577229.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Medium voltage cables are prone to moisture in humid environments, resulting in degradation of insulation performance, increasing the risk of failure and safety hazards, and affecting service life.
The cable core is covered by a twin-screw extruder to form an outer sheath layer to improve the moisture-proof performance of the cable.
It significantly improves the moisture-proof performance of the cable, extends the service life, and reduces the risk of failure and safety risks.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to a moisture-proof and durable medium-voltage cable and a preparation method thereof. Background Art
[0002] Medium voltage cables are cables suitable for power transmission and distribution at medium voltage levels. Typically, the voltage range of medium voltage cables is between 1kV and 35kV. This type of cable is mainly used in urban power grids, industrial facilities, and power transmission systems to effectively transmit power and ensure the stability and reliability of power supply.
[0003] The design and manufacture of medium voltage cables need to meet strict technical standards and safety requirements. They are usually made of copper or aluminum materials with good electrical conductivity, and have multiple layers of insulation and protection to prevent current leakage and interference from the external environment. The structure of medium voltage cables usually includes conductors, insulation layers, shielding layers and outer sheaths, which together ensure the safe operation of cables in various complex environments.
[0004] Due to the importance of medium voltage cables in power systems, it is crucial to select the right cable type and specifications. Different application scenarios and environmental conditions require different cable designs to ensure optimal performance and longest service life. Therefore, when selecting medium voltage cables, it is necessary to comprehensively consider factors such as voltage level, current carrying capacity, laying environment, mechanical strength, and economy.
[0005] During the use of medium-voltage cables, if they are in a humid environment for a long time, moisture will gradually penetrate into the insulation layer of the cable. This phenomenon of moisture will cause the insulation performance of the cable to significantly decrease, making the cable prone to leakage, short circuit and other faults during operation. Cables damaged by moisture will not only affect the stable operation of the power system, but may also bring safety hazards and even cause serious consequences such as fire. Therefore, it is particularly important to improve the moisture resistance of the cable to increase its service life and safety. Summary of the invention
[0006] The object of the present invention is to provide a moisture-proof and durable medium-voltage cable and a preparation method thereof, so as to improve the moisture-proof performance of the cable and avoid the problem that the cable is damaged by moisture and the service life is reduced.
[0007] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a moisture-proof and durable medium-voltage cable, comprising a cable core and an outer sheath layer, the cable preparation method comprising the following steps: S1, taking modified polyethylene resin and dioctyl phthalate and mixing them at 85-95° C. for 10-15 min, then adding moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and kneading at 160-170° C. for 5-6 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder, extruding and coating the outer surface of the cable core, cooling and shaping to form the outer sheath layer coating the outer surface of the cable core, and obtaining the cable; the temperature of the extrusion process is 150-180°C and the screw speed is 60-80rpm.
[0008] As a preferred technical solution of the present invention, the mass ratio of the modified polyethylene resin, dioctyl phthalate, moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 30-40:4-5:3-5:1-2:1-2:1-2:0.4-0.6:0.8:5-7.
[0009] As a preferred technical solution of the present invention, the preparation method of the modified polyethylene resin comprises the following steps: A1. The reactor was evacuated and replaced with nitrogen three times continuously. The reactor was heated and baked with an electric heating gun under vacuum, cooled, ethylene was introduced, and the reactor was heated at a constant temperature. Modified olefin, co-catalyst, and diethyl zinc were added. The reactor was stirred magnetically. The catalyst was dissolved in toluene and flushed into the reactor to carry out polymerization reaction. Acid ethanol was added to the reactor to terminate the reaction. After the polymerization was completed, the reactor was allowed to settle, stirred, and filtered with suction. The filtrate was taken to obtain a modified polyethylene glue. A2, taking the modified polyethylene glue, adding stearic acid amide, heating, ultrasonic mixing and stirring, adding sorbitol, heating, and continuing ultrasonic mixing and stirring to obtain a preparatory solution; A3. Take the preparatory liquid and add it into a twin-screw extruder to extrude and granulate at 170-200° C. to obtain particles. Then, put the particles into a tablet press for compression molding and cool to obtain the modified polyethylene resin.
[0010] As a preferred technical solution of the present invention, in step A1, the amount ratio of ethylene, modified olefin, co-catalyst, diethyl zinc, toluene, catalyst and acid ethanol is 5-10 mol: 4-6 mol: 0.2-0.3 g: 0.05-0.08 g: 10-20 mL: 0.5-0.8 g: 20 mL; the catalyst is N, N'-bis[2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimide (CAS 1616379-43-1); the co-catalyst is tri-n-hexyl aluminum; the acid ethanol refers to adding 5 mL of hydrochloric acid to 15 mL of anhydrous ethanol for acidification, and the concentration of the hydrochloric acid is 0.5 g / mL.
[0011] As a preferred technical solution of the present invention, in step A1, the temperature of the constant temperature heating is 45-55°C; the time of the polymerization reaction is 5-10h; the stirring time after the polymerization is 1-2h; the temperature of the electric heating gun for heating and baking is 600°C, and the baking time is 3min; the cooling refers to cooling to room temperature; the time of the magnetic stirring is 1-2h.
[0012] As a preferred technical solution of the present invention, in step A1, the preparation of the modified olefin comprises the following steps: Add fumaric acid and ethanol into a reaction kettle, heat and stir to dissolve under a nitrogen atmosphere, add isoethyl sulfonic acid, and react under controlled temperature to obtain the modified olefin; the dosage ratio of fumaric acid, isoethyl sulfonic acid, and ethanol is 1-2 mol: 1.5-2.5 mol: 100-200 mL; the heating and stirring refers to stirring at 40-60° C. for 5 min; the temperature-controlled reaction refers to reacting at 60° C. for 30-50 min.
[0013] As a preferred technical solution of the present invention, in step A2, the mass ratio of the modified polyethylene glue, stearic acid amide and sorbitol is 1-2:0.5-0.8:2-4; the heating after adding stearic acid amide refers to heating to 60°C, and the ultrasonic mixing and stirring time after adding stearic acid amide is 0.5-1h; the heating after adding sorbitol refers to heating to 75-80°C, and the ultrasonic mixing and stirring time after adding sorbitol is 20-30min.
[0014] As a preferred technical solution of the present invention, in step A3, the molding pressure is 5 MPa and the molding temperature is 190°C.
[0015] As a preferred technical solution of the present invention, the preparation method of the moisture-proof filler comprises the following steps: B1. Mix lithium fluoride and hydrochloric acid, stir for 30-40 min, add titanium aluminum carbide, stir at 35°C for 20-30 h, centrifuge, wash the solid phase, and dry to obtain material A; the ratio of lithium fluoride, hydrochloric acid, and titanium aluminum carbide is 8-11 g: 200 mL: 10-11 g; the concentration of hydrochloric acid is 9 mol / L; B2. Take the material A, bentonite and N,N-dimethylformamide, mix them, ultrasonically disperse them for 20-30 minutes, add polyvinylidene fluoride, stir them in a 60°C oil bath for 30-40 minutes, dry them in a vacuum environment at 60°C and a vacuum degree of 10Pa for 20 hours, and grind them to obtain the moisture-proof filler; the mass ratio of the material A, bentonite, N,N-dimethylformamide and polyvinylidene fluoride is 1-3:6-8:80:2-4.
[0016] The moisture-proof and durable medium-voltage cable is prepared by the above-mentioned preparation method.
[0017] Beneficial effects of the present invention: The moisture-proof and durable medium-voltage cable and its preparation method disclosed in the present invention improve the thermal stability and intermolecular compactness of polyethylene by preparing highly branched polyethylene molecules; at the same time, a moisture-proof filler with a layer structure with good interface compatibility is introduced to extend the water molecule penetration path, thereby synergistically increasing the moisture-proof performance of the cable. DETAILED DESCRIPTION
[0018] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0019] A method for preparing a moisture-proof and durable medium-voltage cable, comprising a cable core and an outer sheath layer, the cable preparation method comprising the following steps: S1, taking modified polyethylene resin and dioctyl phthalate and mixing them at 85° C. for 10 min, then adding moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and kneading at 160° C. for 5 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder, extruding and coating the outer surface of the cable core, cooling and shaping, forming the outer sheath layer coated on the outer surface of the cable core, and obtaining the cable; the temperature of the extrusion process is 150° C. and the screw speed is 60 rpm; The mass ratio of the modified polyethylene resin, dioctyl phthalate, moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 30:4:3:1:1:1:0.4:0.8:5.
[0020] The preparation method of the modified polyethylene resin comprises the following steps: A1. The reactor was evacuated, and after nitrogen was filled and replaced three times continuously, the reactor was heated and baked with an electric heating gun under vacuum, cooled, ethylene was introduced, and the reactor was heated at a constant temperature. Modified olefin, co-catalyst, and diethyl zinc were added, and magnetic stirring was performed. The catalyst was dissolved in toluene and flushed into the reactor to carry out polymerization reaction. Acid ethanol was added to the reactor to terminate the reaction. After the polymerization was completed, the reactor was allowed to settle, stirred, and filtered by suction. The filtrate was taken to obtain a modified polyethylene glue solution; the dosage ratio of ethylene, modified olefin, co-catalyst, diethyl zinc, toluene, catalyst, and acid ethanol was 5 mol: 4 mol: 0.2 g: 0.05 g: 10 mL: 0.5 g: 20 mL; the catalyst was N, N'-bis[ 2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimide; the cocatalyst is tri-n-hexyl aluminum; the acid ethanol refers to adding 5 mL of hydrochloric acid to 15 mL of anhydrous ethanol for acidification, and the concentration of the hydrochloric acid is 0.5 g / mL; the temperature of the constant temperature heating is 45°C; the polymerization reaction time is 5 hours; the stirring time after the polymerization is completed is 1 hour; the temperature of the electric heat gun heating and baking is 600°C, and the baking time is 3 minutes; the cooling refers to cooling to room temperature; the magnetic stirring time is 1 hour; The preparation of the modified olefin comprises the following steps: fumaric acid and ethanol are added to a reaction kettle, heated and stirred to dissolve under a nitrogen atmosphere, and hydroxyethyl sulfonic acid is added to react under temperature control to obtain the modified olefin; the amount ratio of fumaric acid, hydroxyethyl sulfonic acid and ethanol is 1 mol: 1.5 mol: 100 mL; the heating and stirring refers to stirring at 40° C. for 5 min; the temperature-controlled reaction refers to reacting at 60° C. for 30 min; A2, take the modified polyethylene glue, add stearic acid amide, heat up, ultrasonically mix and stir, add sorbitol, heat up, continue ultrasonically mix and stir, and prepare a preparatory solution; the mass ratio of the modified polyethylene glue, stearic acid amide, and sorbitol is 1:0.5:2; the temperature rise after adding stearic acid amide refers to heating to 60°C, and the ultrasonic mixing and stirring time after adding stearic acid amide is 0.5h; the temperature rise after adding sorbitol refers to heating to 75°C, and the ultrasonic mixing and stirring time after adding sorbitol is 20min; A3. The preparatory liquid is added into a twin-screw extruder and extruded and granulated at 170° C. to obtain particles, and then the particles are placed into a tablet press for compression molding and cooled to obtain the modified polyethylene resin; the compression molding has a compression pressure of 5 MPa and a compression temperature of 190° C.
[0021] The preparation method of the moisture-proof filler comprises the following steps: B1. Mix lithium fluoride and hydrochloric acid, stir for 30 min, add titanium aluminum carbide, stir at 35 ° C for 20 h, centrifuge, wash the solid phase, and dry to obtain material A; the ratio of lithium fluoride, hydrochloric acid, and titanium aluminum carbide is 8g:200mL:10g; the concentration of hydrochloric acid is 9 mol / L; B2. Take the material A, bentonite and N,N-dimethylformamide, mix them, ultrasonically disperse them for 20 minutes, add polyvinylidene fluoride, stir them in a 60°C oil bath for 30 minutes, dry them in a vacuum environment at 60°C and a vacuum degree of 10Pa for 20 hours, and grind them to obtain the moisture-proof filler; the mass ratio of the material A, bentonite, N,N-dimethylformamide and polyvinylidene fluoride is 1:6:80:2.
[0022] A method for preparing a moisture-proof and durable medium-voltage cable, comprising a cable core and an outer sheath layer, the cable preparation method comprising the following steps: S1, taking modified polyethylene resin and dioctyl phthalate and mixing them at 90° C. for 12 min, then adding moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and kneading at 165° C. for 5.5 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder, extruding and coating the outer surface of the cable core, cooling and shaping, forming the outer sheath layer coated on the outer surface of the cable core, and obtaining the cable; the temperature of the extrusion process is 165° C. and the screw speed is 70 rpm; The mass ratio of the modified polyethylene resin, dioctyl phthalate, moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 35:4.5:4:1.5:1.5:1.5:0.5:0.8:6.
[0023] The preparation method of the modified polyethylene resin comprises the following steps: A1. The reactor was evacuated, and after nitrogen was filled and replaced three times continuously, the reactor was heated and baked with an electric heating gun under vacuum, cooled, ethylene was introduced, and constant temperature heating was performed. Modified olefin, co-catalyst, and diethyl zinc were added, and magnetic stirring was performed. The catalyst was dissolved in toluene and flushed into the reactor to carry out polymerization reaction. Acid ethanol was added to the reactor to terminate the reaction. After the polymerization was completed, the reactor was allowed to settle, stirred, and filtered by suction. The filtrate was taken to obtain a modified polyethylene glue solution. The dosage ratio of ethylene, modified olefin, co-catalyst, diethyl zinc, toluene, catalyst, and acid ethanol was 8 mol: 5 mol: 0.25 g: 0.065 g: 15 mL: 0.65 g: 20 mL. The catalyst was N, N'-bis[ 2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimide; the cocatalyst is tri-n-hexyl aluminum; the acid ethanol refers to adding 5 mL of hydrochloric acid to 15 mL of anhydrous ethanol for acidification, and the concentration of the hydrochloric acid is 0.5 g / mL; the temperature of the constant temperature heating is 50°C; the time of the polymerization reaction is 8 hours; the stirring time after the polymerization is completed is 1.5 hours; the temperature of the electric heat gun heating and baking is 600°C, and the baking time is 3 minutes; the cooling refers to cooling to room temperature; the time of the magnetic stirring is 1.5 hours; The preparation of the modified olefin comprises the following steps: fumaric acid and ethanol are added to a reaction kettle, heated and stirred to dissolve under a nitrogen atmosphere, and hydroxyethyl sulfonic acid is added, and the temperature is controlled to react to obtain the modified olefin; the amount ratio of fumaric acid, hydroxyethyl sulfonic acid and ethanol is 1.5 mol: 2 mol: 150 mL; the heating and stirring refers to stirring at 50° C. for 5 min; the temperature-controlled reaction refers to reacting at 60° C. for 40 min; A2, take the modified polyethylene glue, add stearic acid amide, heat up, ultrasonically mix and stir, add sorbitol, heat up, continue ultrasonically mix and stir, and prepare a preparatory solution; the mass ratio of the modified polyethylene glue, stearic acid amide, and sorbitol is 1.5:0.65:3; the temperature rise after adding stearic acid amide refers to heating to 60°C, and the ultrasonic mixing and stirring time after adding stearic acid amide is 0.8h; the temperature rise after adding sorbitol refers to heating to 78°C, and the ultrasonic mixing and stirring time after adding sorbitol is 25min; A3. The preparatory liquid is added into a twin-screw extruder and extruded and granulated at 185° C. to obtain particles, and then the particles are placed into a tablet press for compression molding and cooled to obtain the modified polyethylene resin; the compression molding has a compression pressure of 5 MPa and a compression temperature of 190° C.
[0024] The preparation method of the moisture-proof filler comprises the following steps: B1. Mix lithium fluoride and hydrochloric acid, stir for 35 min, add titanium aluminum carbide, stir at 35 ° C for 25 h, centrifuge, wash the solid phase, and dry to obtain material A; the ratio of lithium fluoride, hydrochloric acid, and titanium aluminum carbide is 9.5g:200mL:10.5g; the concentration of hydrochloric acid is 9mol / L; B2. Take the material A, bentonite and N,N-dimethylformamide, mix them, ultrasonically disperse them for 25 minutes, add polyvinylidene fluoride, stir them in a 60°C oil bath for 35 minutes, dry them in a vacuum environment at 60°C and a vacuum degree of 10Pa for 20 hours, and grind them to obtain the moisture-proof filler; the mass ratio of the material A, bentonite, N,N-dimethylformamide and polyvinylidene fluoride is 2:7:80:3.
[0025] A method for preparing a moisture-proof and durable medium-voltage cable, comprising a cable core and an outer sheath layer, the cable preparation method comprising the following steps: S1, taking modified polyethylene resin and dioctyl phthalate and mixing them at 95° C. for 15 min, then adding moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and kneading at 170° C. for 6 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder, extruding and coating the outer surface of the cable core, cooling and shaping, forming the outer sheath layer coated on the outer surface of the cable core, and obtaining the cable; the temperature of the extrusion process is 180° C. and the screw speed is 80 rpm; The mass ratio of the modified polyethylene resin, dioctyl phthalate, moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 40:5:5:2:2:2:0.6:0.8:7.
[0026] The preparation method of the modified polyethylene resin comprises the following steps: A1. The reactor was evacuated, and after nitrogen was filled and replaced three times continuously, the reactor was heated and baked with an electric heating gun under vacuum, cooled, ethylene was introduced, and constant temperature heating was performed. Modified olefin, co-catalyst, and diethyl zinc were added, and magnetic stirring was performed. The catalyst was dissolved in toluene and flushed into the reactor to carry out polymerization reaction. Acid ethanol was added to the reactor to terminate the reaction. After the polymerization was completed, the reaction was settled, stirred, and filtered by suction. The filtrate was taken to obtain a modified polyethylene glue solution. The dosage ratio of ethylene, modified olefin, co-catalyst, diethyl zinc, toluene, catalyst, and acid ethanol was 10 mol: 6 mol: 0.3 g: 0.08 g: 20 mL: 0.8 g: 20 mL. The catalyst was N, N'-bis[ 2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimide; the cocatalyst is tri-n-hexyl aluminum; the acid ethanol refers to adding 5 mL of hydrochloric acid to 15 mL of anhydrous ethanol for acidification, and the concentration of the hydrochloric acid is 0.5 g / mL; the temperature of the constant temperature heating is 55°C; the time of the polymerization reaction is 10 hours; the stirring time after the polymerization is completed is 2 hours; the temperature of the electric heat gun heating and baking is 600°C, and the baking time is 3 minutes; the cooling refers to cooling to room temperature; the time of the magnetic stirring is 2 hours; The preparation of the modified olefin comprises the following steps: Add fumaric acid and ethanol into a reaction kettle, heat and stir to dissolve under nitrogen atmosphere, add isethionic acid, and react under temperature control to obtain the modified olefin; the ratio of fumaric acid, isethionic acid, and ethanol is 2 mol:2.5 mol:200 mL; the heating and stirring refers to stirring at 60°C for 5 min; the temperature control reaction refers to reacting at 60°C for 50 min; A2. Take the modified polyethylene glue, add stearic acid amide, heat up, ultrasonically mix and stir, add sorbitol, heat up, and continue ultrasonically mixing and stirring to obtain a preparatory solution; the mass ratio of the modified polyethylene glue, stearic acid amide, and sorbitol is 2:0.8:4; the temperature increase after adding stearic acid amide refers to heating to 60°C, and the ultrasonic mixing and stirring time after adding stearic acid amide is 1h; the temperature increase after adding sorbitol refers to heating to 80°C, and the ultrasonic mixing and stirring time after adding sorbitol is 30min; A3, taking the preparatory liquid and adding it into a twin-screw extruder to extrude and granulate at 200°C to obtain particles, and then putting the particles into a tablet press for compression molding, cooling, and obtaining the modified polyethylene resin; the compression molding molding pressure is 5MPa, and the compression temperature is 190°C.
[0027] The preparation method of the moisture-proof filler comprises the following steps: B1. Mix lithium fluoride and hydrochloric acid, stir for 40 min, add titanium aluminum carbide, stir at 35 ° C for 30 h, centrifuge, wash the solid phase, and dry to obtain material A; the ratio of lithium fluoride, hydrochloric acid, and titanium aluminum carbide is 11 g: 200 mL: 11 g; the concentration of hydrochloric acid is 9 mol / L; B2. Take the material A, bentonite and N,N-dimethylformamide, mix them, ultrasonically disperse them for 30 minutes, add polyvinylidene fluoride, stir them in a 60°C oil bath for 40 minutes, dry them in a vacuum environment at 60°C and a vacuum degree of 10Pa for 20 hours, and grind them to obtain the moisture-proof filler; the mass ratio of the material A, bentonite, N,N-dimethylformamide and polyvinylidene fluoride is 3:8:80:4.
[0028] Comparative Example 1 A method for preparing a moisture-proof and durable medium-voltage cable, comprising a cable core and an outer sheath layer, the cable preparation method comprising the following steps: S1. Take polyethylene resin (commercially available, Shanghai Dingfen Chemical Technology Co., Ltd.) and dioctyl phthalate and mix them at 90° C. for 12 min, then add moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and knead at 165° C. for 5.5 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder, extruding and coating the outer surface of the cable core, cooling and shaping, forming the outer sheath layer coated on the outer surface of the cable core, and obtaining the cable; the temperature of the extrusion process is 165° C. and the screw speed is 70 rpm; The mass ratio of the polyethylene resin, dioctyl phthalate, moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 35:4.5:4:1.5:1.5:1.5:0.5:0.8:6.
[0029] The preparation method of the moisture-proof filler comprises the following steps: B1. Mix lithium fluoride and hydrochloric acid, stir for 35 min, add titanium aluminum carbide, stir at 35 ° C for 25 h, centrifuge, wash the solid phase, and dry to obtain material A; the ratio of lithium fluoride, hydrochloric acid, and titanium aluminum carbide is 9.5g:200mL:10.5g; the concentration of hydrochloric acid is 9mol / L; B2. Take the material A, bentonite and N,N-dimethylformamide, mix them, ultrasonically disperse them for 25 minutes, add polyvinylidene fluoride, stir them in a 60°C oil bath for 35 minutes, dry them in a vacuum environment at 60°C and a vacuum degree of 10Pa for 20 hours, and grind them to obtain the moisture-proof filler; the mass ratio of the material A, bentonite, N,N-dimethylformamide and polyvinylidene fluoride is 2:7:80:3.
[0030] Comparative Example 2 A method for preparing a moisture-proof and durable medium-voltage cable, comprising a cable core and an outer sheath layer, the cable preparation method comprising the following steps: S1, taking modified polyethylene resin and dioctyl phthalate and mixing them at 90° C. for 12 min, then adding antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and kneading at 165° C. for 5.5 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder, extruding and coating the outer surface of the cable core, cooling and shaping, forming the outer sheath layer coated on the outer surface of the cable core, and obtaining the cable; the temperature of the extrusion process is 165° C. and the screw speed is 70 rpm; The mass ratio of the modified polyethylene resin, dioctyl phthalate, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 35:4.5:1.5:1.5:1.5:0.5:0.8:6.
[0031] The preparation method of the modified polyethylene resin comprises the following steps: A1. The reactor was evacuated, and after nitrogen was filled and replaced three times continuously, the reactor was heated and baked with an electric heating gun under vacuum, cooled, ethylene was introduced, and constant temperature heating was performed. Modified olefin, co-catalyst, and diethyl zinc were added, and magnetic stirring was performed. The catalyst was dissolved in toluene and flushed into the reactor to carry out polymerization reaction. Acid ethanol was added to the reactor to terminate the reaction. After the polymerization was completed, the reactor was allowed to settle, stirred, and filtered by suction. The filtrate was taken to obtain a modified polyethylene glue solution. The dosage ratio of ethylene, modified olefin, co-catalyst, diethyl zinc, toluene, catalyst, and acid ethanol was 8 mol: 5 mol: 0.25 g: 0.065 g: 15 mL: 0.65 g: 20 mL. The catalyst was N, N'-bis[ 2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimide; the cocatalyst is tri-n-hexyl aluminum; the acid ethanol refers to adding 5 mL of hydrochloric acid to 15 mL of anhydrous ethanol for acidification, and the concentration of the hydrochloric acid is 0.5 g / mL; the temperature of the constant temperature heating is 50°C; the time of the polymerization reaction is 8 hours; the stirring time after the polymerization is completed is 1.5 hours; the temperature of the electric heat gun heating and baking is 600°C, and the baking time is 3 minutes; the cooling refers to cooling to room temperature; the time of the magnetic stirring is 1.5 hours; The preparation of the modified olefin comprises the following steps: fumaric acid and ethanol are added to a reaction kettle, heated and stirred to dissolve under a nitrogen atmosphere, and hydroxyethyl sulfonic acid is added, and the temperature is controlled to react to obtain the modified olefin; the amount ratio of fumaric acid, hydroxyethyl sulfonic acid and ethanol is 1.5 mol: 2 mol: 150 mL; the heating and stirring refers to stirring at 50° C. for 5 min; the temperature-controlled reaction refers to reacting at 60° C. for 40 min; A2, take the modified polyethylene glue, add stearic acid amide, heat up, ultrasonically mix and stir, add sorbitol, heat up, continue ultrasonically mix and stir, and prepare a preparatory solution; the mass ratio of the modified polyethylene glue, stearic acid amide, and sorbitol is 1.5:0.65:3; the temperature rise after adding stearic acid amide refers to heating to 60°C, and the ultrasonic mixing and stirring time after adding stearic acid amide is 0.8h; the temperature rise after adding sorbitol refers to heating to 78°C, and the ultrasonic mixing and stirring time after adding sorbitol is 25min; A3. The preparatory liquid is added into a twin-screw extruder and extruded and granulated at 185° C. to obtain particles, and then the particles are placed into a tablet press for compression molding and cooled to obtain the modified polyethylene resin; the compression molding has a compression pressure of 5 MPa and a compression temperature of 190° C.
[0032] Performance Testing The cables prepared in Examples 1-3 and Comparative Examples 1-2 were tested for moisture absorption and thermal stability. The test results are shown in Table 1 below.
[0033] Table 1 Moisture absorption rate (72h, immersed in 70℃ water, %) Oxidation induction time / min Example 1 0.124 121.4 Example 2 0.115 122.7 Example 3 0.118 122.1 Comparative Example 1 0.375 104.8 Comparative Example 2 0.341 113.4 As can be seen from Table 1, the cables prepared by Examples 1-3 of the present application have good anti-penetration and moisture-proof properties and thermal stability; the present application uses a catalyst N,N'-bis[2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimine to pull the modified olefin to perform chain shuttling during the ethylene polymerization process, activates ethylene and forms a coordination bond with the modified olefin to achieve a chain transfer process, thereby inducing alternating distribution copolymerization of ethylene and the modified olefin on the same polymer chain to form a highly branched polymer, increasing the difficulty of polyethylene molecular chain movement, and the highly branched structure hinders the mutual displacement between molecules, thereby improving the thermal stability and intermolecular compactness of polyethylene; at the same time, a moisture-proof filler with a layer structure with good interface compatibility is introduced to extend the water molecule penetration path, thereby synergistically increasing the moisture-proof performance of the cable.
[0034] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a moisture-proof and durable medium voltage cable, comprising a cable core and an outer sheath layer, characterized in that: The preparation method of the cable comprises the following steps: S1, taking modified polyethylene resin and dioctyl phthalate and mixing them at 85-95° C. for 10-15 min, then adding moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin in sequence, and kneading at 160-170° C. for 5-6 min to obtain a mixture; S2, putting the mixed material into a twin-screw extruder to extrude and coat the mixed material on the outer surface of the cable core, cooling and shaping the mixed material to form the outer sheath layer coating the outer surface of the cable core, and obtaining the cable.
2. The method for preparing a moisture-proof and durable medium voltage cable according to claim 1, characterized in that: The mass ratio of the modified polyethylene resin, dioctyl phthalate, moisture-proof filler, antioxidant 1010, zinc stearate, ultraviolet absorber UV-326, methyl tin mercaptan, stearic acid and paraffin is 30-40:4-5:3-5:1-2:1-2:1-2:0.4-0.6:0.8:5-7.
3. The method for preparing a moisture-proof and durable medium voltage cable according to claim 1, characterized in that: The preparation method of the modified polyethylene resin comprises the following steps: A1. The reactor was evacuated and replaced with nitrogen three times continuously. The reactor was heated and baked with an electric heating gun under vacuum, cooled, ethylene was introduced, and the reactor was heated at a constant temperature. Modified olefin, co-catalyst, and diethyl zinc were added. The reactor was stirred magnetically. The catalyst was dissolved in toluene and flushed into the reactor to carry out polymerization reaction. Acid ethanol was added to the reactor to terminate the reaction. After the polymerization was completed, the reactor was allowed to settle, stirred, and filtered with suction. The filtrate was taken to obtain a modified polyethylene glue. A2, taking the modified polyethylene glue, adding stearic acid amide, heating, ultrasonic mixing and stirring, adding sorbitol, heating, and continuing ultrasonic mixing and stirring to obtain a preparatory solution; A3. Take the preparatory liquid and add it into a twin-screw extruder to extrude and granulate at 170-200° C. to obtain particles. Then, put the particles into a tablet press for compression molding and cool to obtain the modified polyethylene resin.
4. The method for preparing a moisture-proof and durable medium voltage cable according to claim 3, characterized in that: In step A1, the amount ratio of ethylene, modified olefin, co-catalyst, diethyl zinc, toluene, catalyst and acid ethanol is 5-10 mol: 4-6 mol: 0.2-0.3 g: 0.05-0.08 g: 10-20 mL: 0.5-0.8 g: 20 mL; the catalyst is N, N'-bis[2,6-bis(diphenylmethyl)-4-methylphenyl]acenaphthene-1,2-diimide; the co-catalyst is tri-n-hexyl aluminum; the acid ethanol refers to adding 5 mL of hydrochloric acid to 15 mL of anhydrous ethanol for acidification, and the concentration of the hydrochloric acid is 0.5 g / mL.
5. The method for preparing a moisture-proof and durable medium voltage cable according to claim 3, characterized in that: In step A1, the temperature of the constant temperature heating is 45-55°C; the time of the polymerization reaction is 5-10h; the stirring time after the polymerization is 1-2h; the temperature of the electric heating gun for baking is 600°C, and the baking time is 3min; the cooling refers to cooling to room temperature; the time of the magnetic stirring is 1-2h.
6. The method for preparing a moisture-proof and durable medium voltage cable according to claim 3, characterized in that: In step A1, the preparation of the modified olefin comprises the following steps: Add fumaric acid and ethanol into a reaction kettle, heat and stir to dissolve under a nitrogen atmosphere, add isethionic acid, and control the temperature to react to obtain the modified olefin; The dosage ratio of fumaric acid, isethionic acid and ethanol is 1-2 mol: 1.5-2.5 mol: 100-200 mL; the heating and stirring refers to stirring at 40-60° C. for 5 min; and the temperature-controlled reaction refers to reacting at 60° C. for 30-50 min.
7. The method for preparing a moisture-proof and durable medium voltage cable according to claim 3, characterized in that: In step A2, the mass ratio of the modified polyethylene glue, stearic acid amide and sorbitol is 1-2:0.5-0.8:2-4; the heating after adding stearic acid amide refers to heating to 60°C, and the ultrasonic mixing and stirring time after adding stearic acid amide is 0.5-1h; the heating after adding sorbitol refers to heating to 75-80°C, and the ultrasonic mixing and stirring time after adding sorbitol is 20-30min.
8. The method for preparing a moisture-proof and durable medium voltage cable according to claim 3, characterized in that: In step A3, the compression molding process has a compression pressure of 5 MPa and a compression temperature of 190°C.
9. The method for preparing a moisture-proof and durable medium voltage cable according to claim 1, characterized in that: The preparation method of the moisture-proof filler comprises the following steps: B1. Mix lithium fluoride and hydrochloric acid, stir for 30-40 min, add titanium aluminum carbide, stir at 35°C for 20-30 h, centrifuge, wash the solid phase, and dry to obtain material A; the ratio of lithium fluoride, hydrochloric acid, and titanium aluminum carbide is 8-11 g: 200 mL: 10-11 g; the concentration of hydrochloric acid is 9 mol / L; B2. Take the material A, bentonite and N,N-dimethylformamide, mix them, ultrasonically disperse them for 20-30 minutes, add polyvinylidene fluoride, stir them in a 60°C oil bath for 30-40 minutes, dry them in a vacuum environment at 60°C and a vacuum degree of 10Pa for 20 hours, and grind them to obtain the moisture-proof filler; the mass ratio of the material A, bentonite, N,N-dimethylformamide and polyvinylidene fluoride is 1-3:6-8:80:2-4.
10. A moisture-proof and durable medium voltage cable made by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
High-temperature heat-stable PE (polyethylene) material and preparation process thereof
CN120923831A